(untitled) (Research, Society and Development, 2024)
Chronic kidney disease (CKD) is defined as the progressive and irreversible loss in the number and function of nephrons for more than 3 months. It is a well-established fact that 82% of CKD patients undergoing hemodialysis experience at least one cutaneous or mucosal alteration, which can negatively impact their quality of life. The aim of this study was to determine the clinical and epidemiological profile of the population with CKD in a hemodialysis service in the Federal District, as well as to evaluate the prevalence of the main dermatological manifestations in these patients. This is a descriptive, retrospective, case series study based on an analysis of medical records, interviews and physical examinations conducted between August 2019 and January 2020. A total of 46 patients were included, with 52% of them being female and the majority aged between 40 and 50. All of the analyzed patients presented dermatological manifestations, with a particular focus on nail alterations (89.6%), xerosis (83.3%), and mucous membrane alterations (77.1%). Studying the clinical and epidemiological profile, as well as cutaneous and mucosal alterations, in these patients is crucial for early diagnosis and intervention.